Occupational safety and health and smaller organisations: research challenges and opportunities. Issue 1 (2nd January 2016) - Pinder, James; Gibb, Alistair; Dainty, Andrew; Jones, Wendy; Fray, Mike; Hartley, Ruth; Cheyne, Alistair; Finneran, Aoife; Glover, Jane; Haslam, Roger; Morgan, Jennie; Waterson, Patrick; et al.
Abstract: Despite the prevalence of small and medium-sized enterprises (SMEs) and micro organisations, comparatively little is known about how such organisations approach occupational safety and health (OSH). Research has tended to present a negative picture of OSH practices in smaller organisations. This paper discusses some of the challenges to researching OSH in SMEs and micro organisations and how these challenges can be overcome. It draws lessons and experiences from a qualitative study involving 149 structured interviews, nine short-term ethnographies and 21 semi-structured interviews with owners and employees in SMEs and micro organisations from a broad cross-section of industry sectors in the UK, including construction, retail, healthcare, logistics and agriculture. Data from the study suggest that the established boundaries between micro, small and medium-sized enterprises are less meaningful in an OSH context – OSH practices are influenced more by the culture of the organisation, the type of work being undertaken and the sector that an organisation operates in. OSH practices in SMEs and micro organisations tend to reflect more informal characteristics of such organisations, with more emphasis (than many larger organisations) on tacit knowledge, learning by doing and improvisation. Such practices should not necessarily be assumed to be unsafe or incompatible with formalised OSH.